Correction of ischemic optic neuropathy in rats by carbamylated darbepoetin - Anna A. Peresypkina (Belgorod National Research University, 2018)
Introduction: The protective effects of carbamylated darbepoetin on the model of ischemic optic neuropathy in rats were revealed. Objectives: To increase the effectiveness of pharmacological correction of experimental ischemic optic neuropathy in an experiment by using carbamylated darbepoetin. Methods: Measuring the microcirculation level in the retina of rats was carried out using laser Doppler flowmetry (LDF). Registration was done by the data acquisition system Biopac-systems MP-150 and AcqKnowledge 4.2 programme. For microscopy and morphometry, the prepared microslides were scanned using Mirax Desk, a computerised archiving and image analysis system. Image analysis and morphometry were carried out by Pannoramic Viewer 1.15.4. Results and discussion: In the group with correction of ischemic optic neuropathy by carbamylated darbepoetin, 300 μg/kg, the microcirculation level increases by 41.9%, p<0.05 in comparison with the control group, but also below the norm values by 20.3%, p<0.05. In the group with correction by recombinant erythropoietin, 50 IU/kg, the microcirculation rate increases by 36.7%, p<0.05 in comparison with the control group and significantly lower - by 23.3%, p<0.05 - in comparison with the group of intact animals. Qualitative and quantitative morphological indices (thickness of retinal layers) helped to reveal a neuroprotective effect of carbamylated darbepoetin to a greater extent than that of recombinant erythropoietin. Conclusion: The obtained data allow drawing a conclusion about partial restoration of blood flow and preservation of neuronal retinal structures when correcting ischemic optic neuropathy in rats with carbamylated darbepoetin to a greater extent than with recombinant erythropoietin.